ANALISIS PIUTANG TAK TERTAGIH DAN DAMPAKNYA TERHADAP LAPORAN KEUANGAN PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK CABANG MANADO - Tampi, Grace Gloria; Elim, Inggriani; Kalalo, Meily Y.B (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
This study aims to determine the impact of the uncollectible receivables on financial statements at PT Bank Rakyat Indonesia (Persero) Tbk Manado Branch. Bad debts are generally loans whose principal installments have passed 91 days from the due date. This study uses a qualitative method. This research was conducted by interviewing the Operations Manager, Marketing Manager, and Credit Section Staff of PT. Bank Rakyat Indonesia (Persero) Tbk Manado Branch. The research obtained results that show the impact of uncollectible receivables affects the financial statements. Thus, the bank calculates the age receivable reserve to determine the amounts of credit provided and determine the amounst of allowance for uncollectible accounts.